Built to last : Successful habits of visionary companies - Jim Collins; Poras, Jerry I (2005 Random House Business Books, 2005)
The best of the best; Clock building, not time telling; No "Tryanny of the OR"; More than profits; Cult like cultures; Good enough never is; Building the vision.
Keywords: General Management